Study on Synthesis, Characterization and Antibacterial Activity of Binuclear Chromium (II) Complexes of New Schiff Base Ligand Derived from Amino Acids - Voguri Haranath Babu; Anna Venkateswara Rao; Ashok More (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
The study of coordination chemistry of these amino acids with metals can provide under- standing the coordination chemistry for the protein at large. Many proteins within the body need metal ions and they are activated or deactivated by metal ions. Eight chromium(II) complexes of type, [Cr(L)(H2O)x]·xH2O (where L= Schiff base ligand) have been synthesized and characterized on the basis of elemental analysis IR, 1H, 13C NMR, mass and electronic spectroscopy, magnetic and conductance measurements. The amino acid Schiff base ligand behaved as a octa dentate ligand. The probable structures of the chromium(II) complexes have been determined, as well as the antibacterial activity of the chromium(II) complexes, which demonstrated moderate to good activity against Gram-positive and Gram-negative bacteria. Chromium (II) complexes with amino Schiff base ligands were prepared and octahedral structures have been assigned to these complexes by analyzing elemental and spectral data.